2020
DOI: 10.1055/s-0040-1713020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Role of Human Saliva as a Testing Biofluid in Point-of-Care Technology

Abstract: Novel coronavirus disease 2019 (COVID-19) outbreak has termed as a controllable pandemic, and the entire world has come to a standstill trying to mitigate the disease with health systems. Health care providers, around the globe, are fighting day and night. Currently, rapid testing is taking place with the help of nasopharyngeal, oropharyngeal swab, bronchoalveolar lavage, sputum, urine, and blood. All these approaches are invasive or embarrassing to the infected person. It is observed that salivary glands are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 45 publications
1
79
0
4
Order By: Relevance
“…Key advantages of the Simplexa™ COVID-19 Direct assay are simple operation procedures, with an all-in-one reagent mix and high-speed of detection in just over an hour, which is significantly faster than the up to seven hours required by traditional extraction followed by amplification technologies, currently used to detect SARS-CoV-2 RNA in OF samples [ 11 , 12 , 13 , 14 , 15 , 16 , 18 ]. Moreover, the test does not require extra-equipment (i.e centrifuges or an extraction system) and technical laboratory infrastructure, being suitable for the field settings and for near-to-patient diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key advantages of the Simplexa™ COVID-19 Direct assay are simple operation procedures, with an all-in-one reagent mix and high-speed of detection in just over an hour, which is significantly faster than the up to seven hours required by traditional extraction followed by amplification technologies, currently used to detect SARS-CoV-2 RNA in OF samples [ 11 , 12 , 13 , 14 , 15 , 16 , 18 ]. Moreover, the test does not require extra-equipment (i.e centrifuges or an extraction system) and technical laboratory infrastructure, being suitable for the field settings and for near-to-patient diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO currently recommends RT-PCR testing using nasopharyngeal (NPS) and oropharyngeal swabs (OPS) as gold standard for SARS-CoV-2 diagnosis and for monitoring viral load [ 4 , 5 ]. OF has been suggested as an alternate clinical sample, easy and safer to collect, minimizing exposure of healthcare workers and could be useful for making a diagnosis and measuring SARS-CoV-2 viral load and viral shedding during the course of the illness and convalescence [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. To et al, demonstrated that SARS-CoV-2 was present in OF specimen of 11 out of 12 patients, with viral load being higher during the first week after symptoms onset and declining thereafter, being detectable until 25 days after symptoms onset (DSO) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…After further exclusion of five studies, only eight studies met the inclusion criteria for this review. [9][10][11][12][13][14][15][16] No studies were found in the bibliographies of the included articles during manual search. The included articles consisted of six case reports, [10][11][12][13][14]16 a retrospective study, 9 and a prospective study.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…13,14 Also, saliva has been proven as a detecting biofluid for viruses such as human immunodeficiency virus, human papillomavirus, hepatitis A, hepatitis C, Ebola, Zika, and the severe acute respiratory syndrome virus family. 15,16 Saliva contains a host of antimicrobial factors including enzymes and antibodies such as salivary immunoglobulin A (sIgA). 8 It is reported that sIgA is one of the main immunoglobulins in the line of defense against pathogens invading mucosal surfaces, 17 enhancing oral immunity by preventing microbial adhesion and bacterial colonization.…”
Section: Introductionmentioning
confidence: 99%
“…7 Currently, rapid detection of SARS-CoV-2 RNA through saliva, blood, nasal pharyngeal swabs, and throat washes is helping in minimizing and controlling its transmission. 8,9 At present, electronic and digital technology has become the inordinate protagonist and is providing valuable information related to controlling the pandemic. 10 Similarly, timely sharing of information without knowing of its legitimacy and scientific basis may lead to significant controversies and misconceptions.…”
Section: Introductionmentioning
confidence: 99%